2019
DOI: 10.11604/pamj.2019.33.136.17149
|View full text |Cite
|
Sign up to set email alerts
|

Shisha smoking in selected nightclubs in Nigeria

Abstract: IntroductionShisha consumption is a growing public health issue all over the globe and public health awareness about its deleterious health consequences is still not sufficiently raised.MethodsIn this location-based study of nightclubs in Ibadan, Nigeria, 633 patrons of selected nightclubs were interviewed in order to obtain information on prevalence, correlates and predictors of shisha smoking.ResultsThe overall prevalence of shisha smoking was 7.1%. The age of initiation into shisha smoking was lower among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…Consistent with findings of the present study, a recent study conducted by Lasebikan et al [3] in an urban city in Nigeria reported higher prevalence of smoking among night clubbers than non-clubbers [3]. Induction of inflammation and subclinical atherosclerosis are the postulated patho-physiological mechanisms of smoking-induced CVD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with findings of the present study, a recent study conducted by Lasebikan et al [3] in an urban city in Nigeria reported higher prevalence of smoking among night clubbers than non-clubbers [3]. Induction of inflammation and subclinical atherosclerosis are the postulated patho-physiological mechanisms of smoking-induced CVD.…”
Section: Discussionsupporting
confidence: 91%
“…Though later banned, clubbing was later revived in 1933 after which night clubbing spread throughout the world including Asia, Europe, Africa as well as Australia [2]. In Nigeria , there is a rapid proliferation of club's houses/discotheques and drinking points/bars which offer entertainment for not only adolescents and young adults, but also across other age groups and gender [3,4] and those of legal drinking and smoking age of 18+ [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings on shisha use differ from those of a related study in a poor urban community in Johannesburg which reported 60% of high school students ever used, while 20% were daily users 25 . Similar studies conducted in Nigeria and Rwanda (Kigali) reported a shisha prevalence of 7.1% 26 and 20.8% 27 , respectively. The reasons for the use of shisha were not different from other findings where participants believed shisha is a safer alternative to cigarette smoking, and used it out of curiosity and peer influence 23,24,26,27 .…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, urban areas are cities with a higher fund allocation [25]. This sampling method increases accessibility grassroots information within the community as was similarly adopted in another study, not part of the current study shisha smoking in selected nightclubs in Nigeria [26].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…We assessed respondent’s readiness to quit: pre - contemplation, contemplation, preparation, action, and maintenance [32]. The profoma used to determine readiness to quit was similar to our previous study on shisha smoking in selected nightclubs in Nigeria [26].…”
Section: Methodsmentioning
confidence: 99%